Open Access Availability of Indias Scientific Research Funded by National and International Agencies - Deori, Maya; Verma, Manoj Kumar; Nazim, Mohammad (DESIDOC Journal of Library & Information Technology, 2022)
Funding has become the most significant element of supportive action for research that has served the research community in numerous ways to improve the advancement and development of society. Scientific research in India is funded by many public and corporate sector institutions and autonomous organisations, NGOs, and regional and international agencies. However, access to publicly funded scientific research literature has been an essential issue of debate among the advocates of the Open Access (OA) movement during the last two decades. This study maps OA availability to India’s research publications funded by national and international agencies. The study applied a scientometric approach using the Scopus database to identify funding research publications available in the OA domain. The findings revealed that 570320 research articles were published by the Indian researchers during 2016-to 2020, of which 150638 (26.41 %) were produced with the financial support of different national and international funding agencies. Of the funded research publications, 44166 (29.32 %) articles were freely available OA to the public with no or fewer restrictions for reuse. Most of the funded research literature is available via green routes of OA, followed by gold and bronze OA. The study also showed that Horizon 2020 and the Ministry of Science, ICT, and Future Planning are the primary funding sources for researchers in India during study period. The study’s findings are helpful for researchers and policymakers to promote OA availability of funded research to researchers for advancing the country’s scientific progress.